2016
DOI: 10.1002/aenm.201502130
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linked Chitosan as a Polymer Network Binder for an Antimony Anode in Sodium‐Ion Batteries

Abstract: the limited content of Sb in the composites and the low capacity of carbon materials.Polymer binders that contain carboxyl groups and their derivatives, such as poly(acrylic acid) and sodium carboxymethyl cellulose (CMC), have been reported to suppress suffi ciently the reduction of electrolytes and, therefore, to enable better electrochemical performances of anode materials for sodiumion batteries than the polymer binder of poly(vinylidene fl uoride) (PVDF). [25][26][27][28] However, the repeated volume chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 59 publications
(116 reference statements)
1
73
0
1
Order By: Relevance
“…Goodenough and co‐workers also reported the use of a cross‐linked chitosan binder for use with a Sb‐based alloy . Instead of using CMC, the authors relied on chitin and its deacetylated derivative of chitosan, as the basis for the binder.…”
Section: Bindersmentioning
confidence: 99%
“…Goodenough and co‐workers also reported the use of a cross‐linked chitosan binder for use with a Sb‐based alloy . Instead of using CMC, the authors relied on chitin and its deacetylated derivative of chitosan, as the basis for the binder.…”
Section: Bindersmentioning
confidence: 99%
“…As a typical NASICON structure material, Na 3 V 2 (PO 4 ) 3 (NVP) is widely deemed to be a promising candidate for SIFCs, owing to the stable open‐frameworks structure and high operating voltage of 3.4 V . Jian et al reported the detailed structure of rhombohedral Na 3 V 2 (PO 4 ) 3 and its sodium extracted phase of NaV 2 (PO 4 ) 3 .…”
Section: Non‐aqueous Cathode‐based Sifcsmentioning
confidence: 99%
“…As a typical NASICON structure material, Na 3 V 2 (PO 4 ) 3 (NVP) is widely deemed to be a promising candidate for SIFCs, owing to the stable open-frameworks structure and high operating voltage of 3.4 V. [87][88][89][90] Jian et al [91] reported the detailed structure of rhombohedral Na 3 V 2 (PO 4 ) 3 and its sodium extracted phase of NaV 2 (PO 4 ) 3 . It is confirmed that there are two different types of Na sites (6b, M1 and 18e, M2) with different coordination environments in www.small-journal.com 3 .…”
Section: Phosphatesmentioning
confidence: 99%
“…[81][82][83][84][85][86][87][88] In a standard rechargeable battery, energy-storage relevant materials including electrochemically active materials, binder and separator are usually adopted. [89][90][91][92] Inspired by natural systems, scientists have made great progress in the development of these materials in recent years. [93][94][95][96] More specifically, some redox-active molecules and electron shuttles belonging to the biological extracellular electron transfer chains for active respiration have inspired the construction of active electrode materials containing identical redox-active groups.…”
Section: Nature-inspired Energy-storage Related Materialsmentioning
confidence: 99%